Polyacrylonitrile–poly(1‐vinyl pyrrolidone‐co‐vinyl acetate) blend based gel polymer electrolytes incorporated with sodium iodide salt for dye‐sensitized solar cell applications - Saidi, Norshahirah Mohamad; Ng, Hong Ming; Omar, Fatin Saiha; Bashir, Shahid; Ramesh, Kasi; Ramesh, Subramaniam (Wiley, 2019)
New gel polymer electrolytes (GPEs) were prepared via the blending of a polyacrylonitrile polymer and a poly(1-vinyl pyrrolidone-co-vinyl acetate) copolymer. The sodium iodide (NaI) salt concentration was varied for each GPE sample. From ionic conductivity (σ) studies, we observed that the sample with a 40 wt % NaI salt content (N40) showed the highest σ of 3.54 × 10 −3 ± 0.05 S/cm at room temperature, and all of the GPE samples obeyed Arrhenius behavior. The dielectric properties of the GPE samples were also analyzed to study the electrical polarization of the materials. The developed GPE samples were also characterized with X-ray diffraction and Fourier transform infrared spectroscopy. We also then used the developed GPE samples for the fabrication of dye-sensitized solar cells by sandwiching them between a photoanode and Pt counter electrode for photovoltaic studies. The highest photovoltaic performance was achieved by N40, with an efficiency of 3.04%. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47810. © 2019 Wiley Periodicals, Inc.